TINJAUAN HUKUM TERHADAP PERAN PIALANG ASURANSI DALAM PELAKSANAAN ASURANSI PADA PT. ESTIKA JASATAMA DALAM PENYELESAIAN KLAIM NASABAH ASURANSI KERUGIAN - Wira Wijaya, Ryan Nugraha; Ismi, Hayatul; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Insurance broker or broker insurance is a person who works at an insurance brokerage company and meets the requirements to provide recommendations or represent policyholders, insured, or participants in closing insurance or sharia insurance and / or claim settlement. The insurance broker is not only a liaison between the insured and the insurance company, but also provides consulting services for prospective insured. Because the prospective insured could still be confused choosing the right insurance company according to the risk profile.This type of research can be classified in the type of sociological (empirical) legal research, because in this study the authors directly conduct research at the location or place of study in order to provide a complete and clear picture of the problem under study. This research was conducted at PT. Estika Jasatama Pekanbaru, because the location is the author's value is relevant to the title raised by the author, while the population and sample are the company PT. Estika Jasatama, the customer who submitted the claim to the insurance party, and the Insurance Company. Data sources used are primary data and secondary data. Data collection techniques in this study were interviews, and literature review.The conclusions that can be obtained from the results of the study are First, the role of the insurance broker PT. Estika Jasatama in settling customer claims is not optimally run. The broker does not carry out its responsibilities in handling insurance claims settlement and cannot optimize the fair compensation value through a negotiation process with the insurance company. So that customers do not get insurance claims as they should. and Second, the cause of the insurance party does not pay insurance claims to the customer caused by insurance brokers who do not carry out and fulfill their obligations to the parties in the case of this study. Broker's mistakes are less thorough in carrying out the insurance closure process until the settlement of the claim so that the claim is not paid according to what is stated in the insurance policy to the parties.Keywords: Legal Review, Role, Insurance Brokers, Settlement of Claims, Insurance, Losses.